Analysis of the external acoustic meatus for ergonomic design: part I – measurement of the external acoustic meatus using casting, scanning and rapid estimation approaches. Issue 5 (4th May 2021) - Fan, Hao; Yu, Suihuai; Wang, Mengcheng; Li, Mei; Chu, Jianjie; Yan, Yishu; Zhang, Shuai; Chen, Dengkai; Harris-Adamson, Carisa
Abstract: Numerous ear-related wearables require precise measurements of the external acoustic meatus (EAM) to optimise function and comfort. The purpose of this study is to describe a novel methodology for measuring the EAM. A total of 23 measurement variables (18 novel) of the EAM from the entrance to the second bend were collected on 700 Chinese subjects (age: 15–83) using casting and 3D scanning over seven age spans: 10, 20, 30, 40, 50, 60 s and 70+. The ear horizontal plane was identified as a new reference plane for measurements and the medial concha was selected as the reference point for positioning the entrance. A detailed approach to characterising the EAM was developed as was an approach for the rapid estimation of circumference and area using regression equations making it ideal for use in early design conceptualizations. Practitioner summary: This study provides a scalable measurement methodology for determining anthropometric measurements of the external acoustic meatus. The measurement methodology and its application to the design and fitting of ear-related wearables are important to optimising their function and comfort.